Dekonstruksi Pendidikan Agama Kristen bagi Generasi Z - Masinambow, Yornan (Sekolah Tinggi Teologi Transformasi Indonesia, 2022)
Abstract: The purpose of this study is to describe and then analyze Christian Religious Education for generation Z using deconstruction theory and approach. Generation Z is synonymous with digital technology, social media with characteristics of creativity, freedom, hypertolerance, multitasking, and so on. The problem is that Christian Education is still supported by the rigid, indoctrinal, authoritative nature that limits the creativity of generation Z. One way that needs to be done is through the deconstruction of Christian Education. Deconstruction is radically dismantling every event, rejecting centralization. This research uses a descriptive qualitative method with a literature review related to the discussion of deconstruction and Generation Z. The result of this research is that Christian Education through the curriculum, learning process, and pedagogical components must be deconstructed with communicative offers relevant to generation Z. This means that educators must disarm their authoritarian thoughts that are rigid and unfriendly to generation Z and continue to upgrade themselves so that digital technology, social media is also part of educators to be able to adapt in conducting friendly and equal communication.Abstrak: Tujuan dari penelitian ini adalah mendeskripsikan kemudian menganalisis Pendidikan Agama Kristen bagi generasi Z dengan menggunakan teori dan pendekatan dekonstruksi. Generasi Z identik dengan teknologi digital, media sosial dengan karakteristik kreativitas, bebas, hipertoleransi, multitasking, dan lain sebagainya. Masalahnya adalah PAK masih terkukung dengan sifat kaku, indoktriner, otoritatif yang membatasi kreativitas generasi Z. Salah satu cara yang perlu dilakukan adalah melalui dekonstruksi PAK. Dekonstruksi adalah membongkar secara radikal setiap peristiwa, menolak keterpusatan. Penelitian ini menggunakan metode kualitatif deskriptif dengan kajian kepustakaan terkait pembahasan dekonstruksi dan generasi Z. Hasil dari penelitian ini adalah PAK melalui komponen kurikulum, proses pembelajaran, dan pedagogik harus didekonstruksi dengan tawaran komunikatif yang relevan dengan generasi Z. Ini berarti para pendidik harus melucuti pikiran otoriter mereka yang kaku dan tidak bersahabat dengan generasi Z serta terus meng-upgrade diri agar teknologi digital, media sosial juga menjadi bagian dari pendidik untuk dapat beradaptasi dalam melakukan komunikasi ramah dan setara.